Gauging Technology Use in Pre-K -12 Classrooms - Russell Meigs (The Advocate, 2011)
While research in the field of education suggests teachers are using technology more frequently, a tool for gauging this use was needed to provide educators with feedback regarding best practices. This study focused on the development and pilot of an Instrument for measuring levels of integration within constructivist learning environments as noted by the indicators in the Technology Integration Matrix (TIM) model. Analyses conducted in the study showed the questionnaire to be a highly valid and reliable instrument in terms of measuring the model. Recommendations were made for its use in Pre-K - 12 settings as well as in teacher education.